SNP rs4937333 in the miRNA-5003-Binding Site of the ETS1 3′-UTR Decreases ETS1 Expression - Zhang, Ruixian; Pan, Bangpin; Li, Yi; Li, Xiaolan (Frontiers in Genetics, 2019)
Mutations in and reduced expression of the ETS1 gene may be associated with systemic lupus erythematosus (SLE). Here, we report a replication study to investigate associations of eight ETS1 single-nucleotide polymorphisms in the 3′-untranslated region (3′-UTR) with SLE and their regulation of ETS1 expression in a study population. We found that the rs4937333 T allele was associated with a significantly increased risk of SLE (odds ratio: 1.800, 95% confidence interval: 1.02–3.157, P = 0.040) and with dramatically reduced levels of ETS1 in B cells from SLE subjects. Functionally, the rs4937333 T allele alters the binding affinity between miR-5003 and its ETS1 3′-UTR target, thus enhancing suppression of ETS1 expression. Furthermore, immunoglobulin M-secreting plasmacytes were significantly reduced among B cells with the rs4937333 C allele versus the T allele according to FACS and ELISA. Additionally, miR-5003 expression was higher in B cells than in T cells from SLE patients, and a negative correlation between miR-5003 and ETS1 was found, especially in B cells with the T allele. These findings suggest that the rs4937333 T allele is a risk factor for susceptibility to SLE in the studied population. The rs4937333 T allele may enhance the binding of miR-5003 to ETS1, which probably promotes the involvement of ETS1 in the differentiation of B cells into plasmacytes.